DESCRIPTIONS OF BACK PAIN REVEAL UNDERLYING PATHOLOGY BEHIND ACUTE MENINGITIS. Issue 12 (15th November 2016) - Morgan, Catherine; Fuller, Geraint
Abstract : This is the case of a 72-year-old man who presented with bilateral leg weakness and urinary retention four days after developing back pain and confusion. On examination he had no power in his lower limbs and his anal tone was lax. His conscious level quickly deteriorated on arrival to hospital and he was intubated. An MRI of the whole neural axis revealed changes consistent with acute and severe cerebral meningitis. Repeated cerebrospinal fluid analysis did not reveal an organism. He improved with anti-bacterial treatment. Two months later, having complained of intermittent back and leg discomfort which had been investigated with plain radiograph and treated with analgesia, an MRI of the spine was performed which showed discitis. A subsequent echocardiogram discovered subacute bacterial endocarditis, which was thought to have caused the initial septic illness with meningitis through haematogenous spread. Despite extensive investigation, no causative pathogen was ever found. He received further antibiotic treatment and continued to improve. This case illustrates the importance of listening carefully to symptom description even if the patient is improving. It also highlights how initial symptoms at presentation can be overlooked but may be vital to achieve an accurate unifying diagnosis in a complex case.